A Chromosome-Level Genome Assembly of Yellowtail Kingfish (Seriola lalandi) - Li, Shuo; Liu, Kaiqiang; Cui, Aijun; Hao, Xiancai; Wang, Bin; Wang, Hong-Yan; Jiang, Yan; Wang, Qian; Feng, Bo; Xu, Yongjiang; Shao, Changwei; Liu, Xuezhou (Frontiers in Genetics, 2022)
Yellowtail kingfish (Seriola lalandi) is a pelagic marine piscivore with a circumglobal distribution. It is particularly suitable for open ocean aquaculture owing to its large body size, fast swimming, rapid growth, and high economic value. A high-precision genome is of great significance for future genetic breeding research and large-scale aquaculture in the open ocean. PacBio, Illumina, and Hi-C data were combined to assemble chromosome-level reference genome with the size of 648.34 Mb (contig N50: 28.52 Mb). 175 contigs was anchored onto 24 chromosomes with lengths ranging from 12.28 to 34.59 Mb, and 99.79% of the whole genome sequence was covered. The BUSCOs of genome and gene were 94.20 and 95.70%, respectively. Gene families associated with adaptive behaviors, such as olfactory receptors and HSP70 gene families, expanded in the genome of S. lalandi. An analysis of selection pressure revealed 652 fast-evolving genes, among which mkxb, popdc2, dlx6, and ifitm5 may be related to rapid growth traits. The data generated in this study provide a valuable resource for understanding the genetic basis of S. lalandi traits.